Experimental study of alternative tire pyrolysis oil performance operating in single cylinder diesel engine - Mohammad Shafei, Ramli (2013)
This thesis deals with alternative Tire Pyrolysis Oil (TPO) and diesel fuel that will be use to find out the different performance on single cylinder diesel engine by both fuels. The objective of this thesis is to find out the performance of single cylinder diesel engine in term of torque and power and also to find out the fuel consumption of each fuel. Engine use is YANMAR TF120M that has maximum 12 hp. The thesis then describe on how doing the experiment. Performance of the engine experiment is doing by several engine speeds and the performance of torque and power will be find out automatically by using TFX software. The fuel consumption is measure by calculating the volume flow rate of the fuel by time. By getting this result, the comparison between both fuels can be made and then will figure out either TPO can replace diesel fuel or not in future. The properties of each fuel are figure out either it will affect t he performance or not. In diesel fuel engine there are commonly problem that can be occur which is knocking effect and ignition delay. This thesis then will explain detail about the effect of this problem to performance of diesel engine.